Anais Estendidos Do XII Simpósio Brasileiro De Engenharia De Sistemas Computacionais (SBESC Estendido 2022) 2022
DOI: 10.5753/sbesc_estendido.2022.228152
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of low-cost sensors for real-time water quality monitoring

Abstract: Low-cost sensors have the potential to significantly reduce costs compared to reference devices. The problem, however, is that measurements from low-cost sensors can be unreliable when it comes to certifying water quality. This work investigates the possibility of using low-cost sensors to monitor water quality parameters and automate the monitoring process through the concept of the Internet of Things (IoT). The sensors evaluated are turbidity, temperature, dissolved oxygen and hydrogen potential. The evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…RuthEllen et al, (2011) also found that water parameter testing strips were highly inaccurate while electronic meters were the most accurate but costly and require greater degree of care and maintenance. The findings of this study align with the research conducted by Xavier et al (2022), which assessed the data obtained from a turbidity sensor (DFRobot turbidity sensor SEN0189) in comparison to a reference device. The study revealed that during the initial 8-hour test period, the SEN0189 provided results closely resembling those of the reference sensor.…”
Section: Discussionsupporting
confidence: 85%
“…RuthEllen et al, (2011) also found that water parameter testing strips were highly inaccurate while electronic meters were the most accurate but costly and require greater degree of care and maintenance. The findings of this study align with the research conducted by Xavier et al (2022), which assessed the data obtained from a turbidity sensor (DFRobot turbidity sensor SEN0189) in comparison to a reference device. The study revealed that during the initial 8-hour test period, the SEN0189 provided results closely resembling those of the reference sensor.…”
Section: Discussionsupporting
confidence: 85%
“…In his tests, the author reports relative errors of 1.6%. In the work by Xavier et al [33], the LCS SEN0189 only survived immersion for the first 8 hours of a 42-hour test. However, during the 8-hour test phase, the SEN0189 delivered results that were very similar to those of the reference sensor.…”
Section: Experiments With Turbidity Sensorsmentioning
confidence: 99%
“…Without being able to calibrate the DFRobot sensor, the authors therefore decided not to test it. However, an evaluation of the sensor was carried out on [33], where the sensor was found to be fragile when left submerged for long periods and susceptible to infiltration. Section 3.4 describes the results of [33] when the results on turbidity are discussed.…”
Section: Calibration Of Turbidity Sensorsmentioning
confidence: 99%
“…The data collected is diverse and can include variables such as temperature, humidity, geographic location, heart rate, images of open or closed environments, and others. In the context of water quality monitoring, the data collected includes parameters such as potential of Hydrogen, Dissolved Oxygen (DO), turbidity, Oxidation-Reduction Potential (ORP), and others [3][4][5].…”
Section: Introductionmentioning
confidence: 99%